2021
DOI: 10.3390/v13020295
|View full text |Cite
|
Sign up to set email alerts
|

Viral Loads and Disease Severity in Children with Rhinovirus-Associated Illnesses

Abstract: The role of rhinoviruses (RVs) in children with clinical syndromes not classically associated with RV infections is not well understood. We analyzed a cohort of children ≤21 years old who were PCR+ for RV at a large Pediatric Hospital from 2011 to 2013. Using univariate and multivariable logistic regression, we analyzed the associations between demographic, clinical characteristics, microbiology data, and clinical outcomes in children with compatible symptoms and incidental RV detection. Of the 2473 children (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
2
7
2
Order By: Relevance
“…It was reported that the patients co-infected with other respiratory viruses showed higher viral loads than those with HRV mono-infection [ 35 ], but it is not the case in our data. Also, the viral loads wasn’t correlated with the disease severity both in our study and other studies [ 36 , 37 ], while the rates of underlying diseases increased progressively with disease severity, suggesting that host factors bear important responsibility for the disease severity.…”
Section: Discussioncontrasting
confidence: 91%
“…It was reported that the patients co-infected with other respiratory viruses showed higher viral loads than those with HRV mono-infection [ 35 ], but it is not the case in our data. Also, the viral loads wasn’t correlated with the disease severity both in our study and other studies [ 36 , 37 ], while the rates of underlying diseases increased progressively with disease severity, suggesting that host factors bear important responsibility for the disease severity.…”
Section: Discussioncontrasting
confidence: 91%
“…To further investigate the viral load-associated factors, we collected the Ct values of HRV positive samples. It was reported that the patients co-infected with other respiratory viruses showed higher viral loads than those with HRV mono-infection [8], but it is not the case in our data (Fig 6A). Also, the viral loads didn't seem to be correlated with the disease severity (Fig 6B).…”
Section: Hrv Genotypes and Clinical Featurescontrasting
confidence: 85%
“…RV species have different patterns of circulation. Infections occur all year round, but two peaks of infection are classically reported in northern hemisphere countries, the first between April and May, and the second between September and October [28,31]. RV-C could demonstrate a different trend, with a peak of infection during winter months [32].…”
Section: Discussionmentioning
confidence: 96%
“…All these results reinforce the role of RV/EV in LRTI in a clinical scenario of a very young infant in whom this virus is found. RV viral load in the upper respiratory tract has been analysed as a potential biomarker to distinguish between symptomatic patients with respiratory viral infection and asymptomatic carriers of the virus, with heterogenous results [28].…”
Section: Discussionmentioning
confidence: 99%